Level of education, knowledge of pregnant women regarding iron tablets to compliance with their consumption. - Nina Hidayatunnikmah (LLDIKTI Wilayah 1, 2021)
Anemia during pregnancy is one of the problems that can increase maternal and infant morbidity and mortality. The need for iron during pregnancy through daily food is still very little. In this case, the government prevents iron deficiency during pregnancy by providing free iron supplements to all pregnant women, but the benefits of giving iron tablets during pregnancy are often hampered by the compliance of pregnant women in consuming iron tablets. Compliance is a behavior that can be influenced by factors from within the individual, namely education and knowledge. This study aims to determine the relationship between the level of education and knowledge of pregnant women with iron tablets with adherence to consuming iron tablets in the working area of ??Menganti Public Health Center Gresik. The design used in this study was cross sectional and included 60 pregnant women who consumed >90% iron tablets given by the government. The data analysis used was univariate analysis and multivariate analysis using binary logistic regression test, which showed that the level of education and knowledge about iron tablets pregnant women had a significant relationship with adherence to consuming iron tablets (<0.05).